Alkali-resistant glass fiber water dispersible chopped yarn as well as production method and application thereof

By using alkali-resistant glass fiber water dispersed chopped yarn, the problem of poor alkali resistance of medium-alkali and alkali-free glass fibers in cement slurry is solved, and the effect of improving the alkali resistance and service life of cement materials is achieved, reducing the risk of cementing construction.

CN119638204APending Publication Date: 2025-03-18XIANGYANG HUIERJIE GLASSFIBER
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411876623.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Medium alkali and alkali-free glass fibers have poor alkali resistance in cement slurry and are prone to corrosion, making it difficult to meet the requirements of cementing projects.

Method used

The alkali-resistant glass fiber water-dispersed chopped yarn is used to produce alkali-resistant glass fiber yarns through the tank kiln method, and the water-dispersed wetting agent is applied during the drawing process. After natural conditioning, cut into chopped fibers of 3 to 36 mm length.

Benefits of technology

It improves alkali resistance, enhances the leakage resistance and service life of cement materials, reduces the risk of cementing construction, effectively utilizes cement slurry, protects the oil and gas layer, and reduces investment before oil and gas wells are put into production.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to an alkali-resistant glass fiber water dispersible chopped yarn and a production method thereof, and the alkali-resistant glass fiber water dispersible chopped yarn comprises the following components: 58-65% of SiO2; 13.5%-17.5% of ZrO2 (zirconium oxide); 4.5 to 7 percent of CaO; the content of NaO2 is 11.5 to 14.5 percent; 0.5% to 2.5% of K2O; al2O3, less than or equal to 0.5%; less than or equal to 0.3% of Fe2O3; the balance is impurities; a tank furnace method is adopted for production, and alkali-resistant glass fiber yarn with the diameter of 7-15 micrometers is manufactured after high-temperature melting; in the drawing process, the precursor is coated with a water dispersible impregnating compound, and after natural conditioning, the precursor is chopped into chopped yarns with the length of 3-36 mm; the water-dispersible impregnating compound is a polymer emulsion composed of an emulsifier, a penetrant, a surfactant, a metal oxide, a dispersant and water. The anti-leakage cement paste is used in a well cementation cement paste system and cement concrete, so that the stress concentration of internal defects of formed set cement is reduced, the impact resistance is improved, the effects of preventing leakage and prolonging the service life are achieved, and the quality of well cementation and the quality of the concrete are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of production of alkali-resistant glass fiber products. Background Art

[0002] This section merely provides background information related to the present disclosure and is not necessarily prior art.

[0003] Fiber concrete is a new type of composite material and an important field of contemporary concrete modification research. In recent years, the application of fibers represented by steel fibers, synthetic fibers, carbon fibers and glass fibers in cement concrete has been rapidly developed. Fiber concrete is another major breakthrough after reinforced concrete and prestressed concrete. Due to the combined effect of fiber and cement concrete, cement concrete has a series of superior properties, so it has received great attention and favor from the engineering community at home and abroad, and is widely used in various engineering fields. At present, the relevant technology is to use alkali-free and medium-alkali glass fibers in cement slurry to enhance its strength and toughness, thereby making the cement material stronger and more stable. However, the inventors have found that due to the poor alkali resistance of medium-alkali and alkali-free glass fibers, the fibers used in cement slurry are quickly corroded and it is difficult to meet the requirements of cementing projects. Summary of the invention

[0004] The purpose of the present invention is to provide an alkali-resistant glass fiber water-dispersible chopped yarn, which overcomes the weaknesses of medium-alkali and alkali-free glass fibers, fully utilizes the excellent alkali resistance and high dispersibility of the alkali-resistant glass fiber chopped yarn, and is used in cementing and cement concrete environments to improve its alkali resistance and better prevent leakage and increase service life.

[0005] The inventors have found through research that after adding alkali-resistant chopped fibers, it also plays a role in thickening during the process of pumping cement slurry, reducing the loss of cement slurry system. The cement stone formed by adding fibers has good compatibility and adhesion, and thus has anisotropic high toughness. The fibers can shield the stress field at the crack tip of the defect in the cement stone, improve the toughness of the cement stone against fracture, and thus help cementing construction operations to reduce the loss of cement slurry. It not only effectively utilizes cement slurry, but also reduces the risk of cementing construction operations, helps protect oil and gas layers, and reduces the investment before the oil and gas wells are put into production.

[0006] The technical scheme adopted by the present invention is: an alkali-resistant glass fiber water-dispersed chopped yarn, the components of which include: SiO2, 58-65%; ZrO2, 13.5%-17.5%; CaO, 4.5-7%; NaO2, 11.5-14.5%; K2O, 0.5-2.5%; Al2O3, ≤0.5%; Fe2O3, ≤0.3%; the remainder is impurities; the alkali-resistant glass fiber yarn with a diameter of 7-15 μm is produced by a pool kiln method, and is drawn into an alkali-resistant glass fiber yarn with a diameter of 7-15 μm after high-temperature melting; during the drawing process, the raw silk is coated with a layer of water-dispersible impregnation agent, and is naturally conditioned and chopped into chopped yarn with a length of 3-36 mm; The water-dispersible wetting agent is a polymer emulsion composed of an emulsifier, a penetrant, a surfactant, a metal oxide, a dispersant, and water; The component ratio of the polymer emulsion is: Emulsifier: penetrant: surfactant: metal oxide: dispersant: water = 2.5~3.5: 0.6~0.8: 3.5~5: 1~2: 0.03~0.05: 90.

[0007] Preferably, the component ratio of the polymer emulsion is: Emulsifier: penetrant: surfactant: metal oxide: dispersant: water = 3: 0.8: 4: 2: 0.03: 90; Or: Emulsifier: penetrant: surfactant: metal oxide: dispersant: water = 2.5: 0.6: 5: 1.5: 0.05: 90; Or: Emulsifier: penetrant: surfactant: metal oxide: dispersant: water = 3.5:0.7:3.5:1.0:0.04:90.

[0008] The emulsifier is alkylphenol polyoxyethylene ether (brand: emulsifier OP-10); The penetrant is fatty alcohol zinc-based phenol polyoxyethylene ether (brand: JFC-1); The surfactant is a polyoxyethylene ether compound (brand: JFCS); The metal oxide is tin oxide (brand: Sn); The dispersant is carboxymethyl cellulose (brand: HPMC).

[0009] The components include: SiO2, 58.5-61%; ZrO2, 15.5%-17.5%; CaO, 5-7%; NaO2, 12.5-14.5%; K2O, 0.5-2%; Al2O3, ≤0.3%; Fe2O3, ≤0.2%; the remainder is impurities; the diameter of the glass fiber monofilament is 7-15 μm; and the cut length is 3-30 mm.

[0010] The components include: SiO2, 59-62%; ZrO2, 16.0%-17.5%; CaO, 4.5-6%; NaO2, 13.5-14.5%; K2O, 2.0-2.5%; Al2O3, ≤0.5%; Fe2O3, ≤0.3%; the remainder is impurities; the diameter of the glass fiber monofilament is 7-9 μm; and the cut length is 3-20 mm.

[0011] The components include: SiO2, 63-65%; ZrO2, 13.5-14.5%; CaO, 5.5-7%; NaO2, 11.5-13.5%; K2O, 1.0-2.0%; Al2O3, ≤0.2%; Fe2O3, ≤0.2%; the remainder is impurities; the diameter of the glass fiber monofilament is 7-10 μm; and the cut length is 3-36 mm.

[0012] The present invention also provides a method for producing alkali-resistant glass fiber water-dispersible chopped yarns, comprising the following process steps: ⑴ Select the following raw materials in weight ratio: quartz sand: 56-65, sodium sulfate: 1-2, limestone: 5-9, zircon sand: 21-28, soda ash: 18-25, fluorite: 0.5-2; (2) The above raw materials are crushed and mixed, added into a stirrer, stirred evenly, transported to a melting pool using shrinkage-free zirconium corundum bricks as lining or masonry, melted by natural gas, and melted at a high temperature of 1600-1700°C to form alkali-resistant glass fiber yarn with a diameter of 7-15μm and ZrO2 of 14.5-16.0% or more; ⑶ During the wire drawing process, the surface is coated with a water-dispersible wetting agent; (4) The drawn alkali-resistant water-dispersible glass fiber raw yarn is naturally conditioned at room temperature to control its surface moisture content at 2-5%; ⑸ Place the conditioned alkali-resistant glass fiber strands neatly on the creel, draw out the strand heads in turn and place them on the chopper to chop them into 3-36mm long water-dispersible chopped fibers; (6) Quickly put the above water-dispersible chopped fibers into a sealed bag to prevent water from evaporating.

[0013] In step (1), the following raw materials are selected in weight ratio: quartz sand: 60-65, sodium sulfate: 1-1.5, limestone: 5-7, zircon sand: 20-25, soda ash: 18-23, fluorite: 0.5-1.5.

[0014] The component ratio of the polymer emulsion is: Emulsifier: penetrant: surfactant: metal oxide: dispersant: water = 3: 0.8: 4: 2: 0.03: 90; Or: Emulsifier: penetrant: surfactant: metal oxide: dispersant: water = 2.5: 0.6: 5: 1.5: 0.05: 90; Or: Emulsifier: penetrant: surfactant: metal oxide: dispersant: water = 3.5:0.7:3.5:1.0:0.04:90.

[0015] The present invention also provides a method for producing alkali-resistant glass fiber water-dispersible chopped yarns, comprising the following process steps: ⑴ The selected ingredients are: SiO2, 58-65%; ZrO2, 13.5%-17.5%; CaO, 4.5-7%; NaO2, 11.5-14.5%; K2O, 0.5-2.5%; Al2O3, ≤0.5%; Fe2O3, ≤0.3%; the remainder is impurities, and the diameter is 7-15μm of alkali-resistant glass fiber raw yarn; (2) coating a layer of water-dispersible wetting agent on the surface of the alkali-resistant glass fiber precursor, wherein the water-dispersible wetting agent is a polymer emulsion composed of an emulsifier, a penetrant, a surfactant, a reducing agent, a dispersant, and water; ⑶ The drawn alkali-resistant water-dispersible glass fiber raw yarn is naturally conditioned at room temperature to control its surface moisture content at 2-5%; ⑷ Place the conditioned alkali-resistant glass fiber strands neatly on the creel, draw out the strand heads in turn and place them on the chopper to chop them into 3-36mm long water-dispersible chopped fibers; ⑸ Quickly put the above water-dispersible chopped fibers into a sealed bag to prevent water from evaporating.

[0016] The component ratio of the polymer emulsion is: Emulsifier: penetrant: surfactant: metal oxide: dispersant: water = 3: 0.8: 4: 2: 0.03: 90; Or: Emulsifier: penetrant: surfactant: metal oxide: dispersant: water = 2.5: 0.6: 5: 1.5: 0.05: 90; Or: Emulsifier: penetrant: surfactant: metal oxide: dispersant: water = 3.5:0.7:3.5:1.0:0.04:90.

[0017] The present invention also provides an alkali-resistant glass chopped fiber water-dispersible sizing agent, which is composed of an emulsifier, a penetrant, a surfactant, a metal oxide, a dispersant, and water; the component ratio is: Emulsifier: penetrant: surfactant: metal oxide: dispersant: water = 3: 0.8: 4: 2: 0.03: 90; Or: Emulsifier: penetrant: surfactant: metal oxide: dispersant: water = 2.5: 0.6: 5: 1.5: 0.05: 90; Or: Emulsifier: penetrant: surfactant: metal oxide: dispersant: water = 3.5:0.7:3.5:1.0:0.04:90.

[0018] The present invention also provides the use of the above-mentioned alkali-resistant glass fiber water-dispersed chopped yarn in cementing materials and cement concrete. The present invention is used in cementing cement slurry system and cement concrete to reduce the stress concentration of the internal defects of the formed cement stone, thereby improving the impact resistance, preventing leakage and increasing the service life, and effectively improving the quality of cementing and concrete.

[0019] In petroleum engineering construction, fiber is added, that is, short-cut fibers are added to cementing cement slurry. In the solidified cement ring, the short-cut fibers are tightly bonded between cement hydrates, thus playing a "bridging" role and a subtle "reinforcing" role, thereby transmitting stress loads and improving the mechanical deformation capacity of the cement ring, thus improving the cementing quality. A certain proportion of alkali-resistant glass short-cut fibers are added to the cementing cement slurry system, and the load is transmitted by the fibers to reduce the stress concentration of the internal defects of the formed cement stone, thereby improving the impact resistance. The cement stone formed after adding alkali-resistant glass fibers has good compatibility and adhesion, so it has anisotropic high toughness. Fibers can shield the stress field at the crack tip of the defect in the cement stone, improve the toughness of the cement stone against fracture, and cementing after fiber addition has multiple functions. After the fiber is added to the cement slurry, the viscosity is higher and the flow performance is reduced, which is beneficial to the cementing construction operation to reduce the degree of cement slurry loss, not only effectively utilizing the cement slurry, but also reducing the risk of cementing construction operations.

[0020] The operation technology of fracturing with alkali-resistant glass fiber is superior to the resin-coated sand technology, and its technology has a good prospect for promotion and application. Fiber-added fracturing is conducive to meeting the need for initial return fluid without shutting down the well, is conducive to low-permeability reservoir reconstruction operations, especially low-pressure oil and gas layer construction operations, and is also conducive to the promotion and application of high-efficiency breakers and non-breaker working fluids.

[0021] The advantages of the present invention over the prior art are that the technical solution of the present invention has properties that ordinary wetting agents do not have, such as rapid dispersion in water, high dispersibility, and good affinity and bonding with cement substrates; this is due to the good toughening effect of the fiber monofilament dispersant, the extremely low fiber blending amount, but the significant strengthening effect, which can effectively improve the generation of surface cracks and increase strength.

[0022] The water-dispersible chopped yarn provided by the present invention has the characteristic of being quickly dispersed into single fibers when it meets water, and has high water dispersibility. It can be fully dispersed into single fibers 10 seconds after mixing with cement mortar, and can be easily added to the slurry and evenly dispersed. Due to its high dispersibility and thickening effect after meeting the cement slurry, it has a significant effect of enhancing leak repair in cementing. At the same time, this water-dispersible chopped yarn can be mixed into the mortar to make textured decorative mortar, anti-cracking mortar, artificial stone, GRC product surface mortar, repair mortar, self-leveling mortar and other product systems. Compared with chemical fibers, it has the advantages of good bonding with cement substrates, high elastic modulus, no "head exposure", later polishing, and better reinforcement performance.

[0023] The alkali-resistant glass fiber water-dispersible chopped yarn provided by the present invention is mainly used for reinforcing cementitious materials such as cement and gypsum. The fiber dispersion effect is best when the slurry concentration is 4-20%. When the addition amount is greater than 1%, the homogeneity of the board can be greatly improved, the bearing capacity can be increased, and cracking can be prevented. It can be used to make GRC flat panels, asbestos substitutes or less asbestos products, etc.

[0024] The addition of alkali-resistant glass fiber water-dispersible chopped yarn is mainly to increase the fluidity of the slurry and increase the surface area of ​​the fiber. The fluidity is mainly to ensure that the concrete obtains the fluidity required for construction under the condition of low water-binder ratio, reduce the porosity in the concrete, and make the concrete obtain higher density and higher compressive strength. The larger the specific surface area, the more fibers in the same unit volume, and can be more evenly distributed inside the concrete, effectively preventing the expansion of cracks, and enhancing the flexibility and crack resistance of the concrete.

[0025] The alkali-resistant glass fiber water-dispersible chopped yarn provided by the present invention adopts alkali-resistant glass fiber yarn containing zirconium oxide, which is chopped after being drawn and coated with a special water-dispersible impregnating agent. The chopped yarn has the characteristics of being quickly dispersed into single fibers when it meets water, and has high water-dispersibility. It can be fully dispersed into single fibers in 10 seconds after mixing with cement mortar, and is easy to add to the slurry and disperse evenly; due to the high dispersibility and extremely low fiber blending amount, but the reinforcement effect is significant, it can effectively improve the generation of surface cracks and improve the strength of the product. It is especially used in cementing of petroleum engineering technical service projects. After the alkali-resistant chopped fibers are added, it also plays a thickening role in the process of pumping cement slurry, reducing the leakage degree of the cement slurry system. The fiber can shield the stress field of the crack tip at the defect in the cement stone, improve the toughness of the cement stone against fracture, not only effectively utilize the cement slurry, but also reduce the risk of cementing construction operations, which is beneficial to protecting the oil and gas layer and reducing the investment before the oil and gas well is put into production. Compared with chemical fibers, it has the advantages of good bonding with cement slurry, outstanding alkali resistance, high elastic modulus and better reinforcement performance. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without carrying out creative work are within the scope of protection of the present invention.

[0027] Technologies, methods, and apparatus known to ordinary technicians in the relevant field may not be discussed in detail, but where appropriate, such technologies, methods, and apparatus should be considered part of the authorization specification. Embodiment 1:

[0028] The composition of the alkali-resistant glass fiber water-dispersed chopped yarn of Example 1 includes: SiO2, 63~65%; ZrO2, 13.5~14.5%; CaO, 5.5~7%; NaO2, 11.5~13.5%; K2O, 1.0~2.0%; Al2O3, ≤0.2%; Fe2O3, ≤0.2%; the remainder is impurities; the diameter of the glass fiber monofilament is 7~9μm; and it is cut into glass fiber monofilaments with a length of 3~36㎜.

[0029] The production method of the alkali-resistant glass fiber water-dispersible chopped yarn of Example 1 comprises the following process steps: ⑴ Select the following raw materials in weight ratio: quartz sand: 60-65, sodium sulfate: 1.3-1.5, limestone: 5-7, zircon sand: 21-23, soda ash: 18-20, fluorite: 0.5-1.5; (2) The above raw materials are crushed and mixed, added into a stirrer, stirred evenly, transported to a melting pool using shrinkage-free zirconium corundum bricks as lining or masonry, melted in natural gas, and melted at a high temperature of 1600-1700°C to draw into alkali-resistant glass fiber yarn with a diameter of 7-9μm; ⑶ During the wire drawing process, the surface is coated with a water-dispersible impregnation agent; the impregnation agent is a polymer emulsion composed of an emulsifier, a penetrant, a surfactant, a metal oxide, a dispersant, and water. The emulsifier is an alkylphenol polyoxyethylene ether, and the penetrant is a fatty alcohol zinc-based phenol poly; the surfactant is a polyoxyethylene ether compound, the metal oxide is a metal oxide, and the dispersant is carboxymethyl cellulose. The component ratio of the polymer emulsion is: Emulsifier: penetrant: surfactant: metal oxide: dispersant: water = 3: 0.8: 4: 2: 0.03: 90; ⑷ The drawn glass fiber raw yarn needs to be naturally conditioned at room temperature to keep its surface moisture content at 2-5%; ⑸ Arrange the conditioned alkali-resistant raw silk neatly and chop it into 3-36mm long short fibers on a chopping machine; (6) Quickly put the above water-dispersible chopped fibers into a sealed bag to prevent water from evaporating. Embodiment 2:

[0030] The composition of the alkali-resistant glass fiber water-dispersed chopped yarn of Example 2 includes: SiO2, 59-62%; ZrO2, 16.0%-17.5%; CaO, 4.5-6%; NaO2, 13.5-14.5%; K2O, 2.0-2.5%; Al2O3, ≤0.5%; Fe2O3, ≤0.3%; the remainder is impurities; the diameter of the glass fiber monofilament is 7-8.5μm; and it is cut into glass fiber monofilaments with a length of 3-20mm.

[0031] The production method of the alkali-resistant glass fiber water-dispersed chopped yarn of Example 2 comprises the following process steps: ⑴ Use the following raw materials in weight ratio: quartz sand: 59-62, sodium sulfate: 1.0-1.3, limestone: 6-8, zircon sand: 25-28, soda ash: 23-25, fluorite: 1.5-2; (2) The above raw materials are crushed and mixed, added into a stirrer, stirred evenly, transported to a melting pool using shrinkage-free zirconium corundum bricks as lining or masonry, melted in natural gas, and melted at a high temperature of 1600-1700°C to draw into alkali-resistant glass fiber yarn with a diameter of 7-8.5μm; ⑶ During the wire drawing process, the surface is coated with a water-dispersible impregnation agent; the impregnation agent is a polymer emulsion composed of an emulsifier, a penetrant, a surfactant, a metal oxide, a dispersant, and water. The emulsifier is an alkylphenol polyoxyethylene ether, and the penetrant is a fatty alcohol zinc-based phenol poly; the surfactant is a polyoxyethylene ether compound, the metal oxide is a metal oxide, and the dispersant is carboxymethyl cellulose. The component ratio of the polymer emulsion is: Emulsifier: penetrant: surfactant: metal oxide: dispersant: water = 2.5:0.6:5:1.5:0.05:90.

[0032] ⑷ The drawn glass fiber raw yarn needs to be naturally conditioned at room temperature to keep its surface moisture content at 2-5%; ⑸ Arrange the conditioned alkali-resistant raw silk neatly and chop it into 3-20mm long short fibers on a chopping machine; (6) Quickly put the above water-dispersible chopped fibers into a sealed bag to prevent water from evaporating. Embodiment 3:

[0033] The composition of the alkali-resistant glass fiber water-dispersed chopped yarn of Example 3 includes: SiO2, 58.5% to 61%; ZrO2, 15.5% to 17.5%; CaO, 5 to 7%; NaO2, 12.5 to 14.5%; K2O, 0.5 to 2%; Al2O3, ≤0.3%; Fe2O3, ≤0.2%; the remainder is impurities; the diameter of the glass fiber monofilament is 7 to 15 μm; and the cut length is 3 to 30 mm.

[0034] Embodiment 3 The production method of alkali-resistant glass fiber water-dispersible chopped yarn comprises the following process steps: ⑴ Use the following raw materials in weight ratio: quartz sand: 56-59, sodium sulfate: 1.5-1.8, limestone: 7-9, zircon sand: 23-25, soda ash: 20-23, fluorite: 1.0-1.5; (2) The above raw materials are crushed and mixed, added into a stirrer, stirred evenly, transported to a melting pool using shrinkage-free zirconium corundum bricks as lining or masonry, melted in natural gas, and melted at a high temperature of 1600-1700°C to draw into alkali-resistant glass fiber yarn with a diameter of 7-15μm; ⑶ During the wire drawing process, the surface is coated with a water-dispersible impregnation agent; the impregnation agent is a polymer emulsion composed of an emulsifier, a penetrant, a surfactant, a metal oxide, a dispersant, and water. The emulsifier is an alkylphenol polyoxyethylene ether, and the penetrant is a fatty alcohol zinc-based phenol poly; the surfactant is a polyoxyethylene ether compound, the metal oxide is a metal oxide, and the dispersant is carboxymethyl cellulose. The component ratio of the polymer emulsion is: Emulsifier: penetrant: surfactant: metal oxide: dispersant: water = 3.5:0.7:3.5:1.0:0.04:90.

[0035] ⑷ The processed glass fiber raw yarn needs to be naturally conditioned at room temperature to keep its surface moisture content at 2-5%; ⑸ Arrange the conditioned alkali-resistant raw silk neatly and chop it into 3-30mm long short fibers on a chopping machine; (6) Quickly put the above water-dispersible chopped fibers into a sealed bag to prevent water from evaporating. Embodiment 4:

[0036] The composition of the alkali-resistant glass fiber water-dispersed chopped yarn of Example 4 includes: SiO2, 58-65%; ZrO2, 13.5%-17.5%; CaO, 4.5-7%; NaO2, 11.5-14.5%; K2O, 0.5-2.5%; Al2O3, ≤0.5%; Fe2O3, ≤0.3%; the remainder is impurities; the diameter of the glass fiber monofilament is 7-15μm; and the cut length is 3-36㎜.

[0037] Example 4 The production method of alkali-resistant glass fiber water-dispersible chopped yarns includes the following process steps: ⑴ Use the following raw materials in weight ratio: quartz sand: 56-65, sodium sulfate: 1-2, limestone: 5-9, zircon sand: 21-28, soda ash: 18-25, fluorite: 0.5-2; (2) The above raw materials are crushed and mixed, added into a stirrer, stirred evenly, transported to a melting pool using shrinkage-free zirconium corundum bricks as lining or masonry, melted in natural gas, and melted at a high temperature of 1600-1700°C to draw into alkali-resistant glass fiber yarn with a diameter of 7-15μm; ⑶ During the wire drawing process, the surface is coated with a water-dispersible impregnation agent; the impregnation agent is a polymer emulsion composed of an emulsifier, a penetrant, a surfactant, a metal oxide, a dispersant, and water. The emulsifier is an alkylphenol polyoxyethylene ether, and the penetrant is a fatty alcohol zinc-based phenol poly; the surfactant is a polyoxyethylene ether compound, the metal oxide is a metal oxide, and the dispersant is carboxymethyl cellulose. The component ratio of the polymer emulsion is: Emulsifier: penetrant: surfactant: metal oxide: dispersant: water = 3:0.8:4:2:0.03:90.

[0038] ⑷ The processed glass fiber raw yarn needs to be naturally conditioned at room temperature to keep its surface moisture content at 2-5%; ⑸ Arrange the conditioned alkali-resistant raw silk neatly and chop it into 3-36mm long short fibers on a chopping machine; (6) Quickly put the above water-dispersible chopped fibers into a sealed bag to prevent water from evaporating. Embodiment 5:

[0039] Example 5 The production method of alkali-resistant glass fiber water-dispersible chopped yarns includes the following process steps: ⑴ The selected ingredients are: SiO2, 58-65%; ZrO2, 13.5%-17.5%; CaO, 4.5-7%; NaO2, 11.5-14.5%; K2O, 0.5-2.5%; Al2O3, ≤0.5%; Fe2O3, ≤0.3%; the remainder is impurities; alkali-resistant glass fiber strands with a diameter of 7-15μm; (2) coating a layer of water-dispersible wetting agent on the surface of the alkali-resistant glass fiber precursor, wherein the water-dispersible wetting agent is a polymer emulsion composed of an emulsifier, a penetrant, a surfactant, a reducing agent, a dispersant, and water; ⑶ The drawn alkali-resistant water-dispersible glass fiber raw yarn is naturally conditioned at room temperature to control its surface moisture content at 2-5%; ⑷ Place the conditioned alkali-resistant glass fiber strands neatly on the creel, draw out the strand heads in turn and place them on the chopper to chop them into 3-36mm long water-dispersible chopped fibers; ⑸ Quickly put the above water-dispersible chopped fibers into a sealed bag to prevent water from evaporating.

[0040] The above description is only an exemplary embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An alkali-resistant glass fiber water-dispersed chopped strand, characterized in that: Its ingredients include: SiO2, 58-65%; ZrO2, 13.5%-17.5%; CaO, 4.5-7%; NaO2, 11.5-14.5%; K2O, 0.5-2.5%; Al2O3, ≤0.5%; Fe2O3, ≤0.3%; the remainder is impurities; it is produced by the pool kiln method, and after high-temperature melting, it is drawn into an alkali-resistant glass fiber yarn with a diameter of 7-15μm; during the drawing process, the raw silk is coated with a layer of water-dispersible impregnation agent, and after natural conditioning, it is chopped into 3-36mm long chopped yarn; The water-dispersible wetting agent is a polymer emulsion composed of an emulsifier, a penetrant, a surfactant, a metal oxide, a dispersant, and water; The component ratio of the polymer emulsion is: Emulsifier: penetrant: surfactant: metal oxide: dispersant: water = 2.5~3.5: 0.6~0.8: 3.5~5: 1~2: 0.03~0.05:

90.

2. The alkali-resistant glass fiber water-dispersed chopped strands according to claim 1, characterized in that: The emulsifier is alkylphenol polyoxyethylene ether; The penetrant is fatty alcohol zinc-based phenol polyoxyethylene ether; The surfactant is a polyoxyethylene ether compound; The metal oxide is tin oxide; The dispersant is carboxymethyl cellulose.

3. The alkali-resistant glass fiber water-dispersed chopped strands according to claim 1, characterized in that: The components include: SiO2, 58.5-61%; ZrO2, 15.5%-17.5%; CaO, 5-7%; NaO2, 12.5-14.5%; K2O, 0.5-2%; Al2O3, ≤0.3%; Fe2O3, ≤0.2%; the remainder is impurities; the diameter of the glass fiber monofilament is 7-15 μm; and the cut length is 3-30 mm.

4. The alkali-resistant glass fiber water-dispersed chopped strands according to claim 1, characterized in that: The components include: SiO2, 59-62%; ZrO2, 16.0%-17.5%; CaO, 4.5-6%; NaO2, 13.5-14.5%; K2O, 2.0-2.5%; Al2O3, ≤0.5%; Fe2O3, ≤0.3%; the remainder is impurities; the diameter of the glass fiber monofilament is 7-9 μm; and the cut length is 3-20 mm.

5. The alkali-resistant glass fiber water-dispersed chopped strands according to claim 1, characterized in that: The components include: SiO2, 63-65%; ZrO2, 13.5-14.5%; CaO, 5.5-7%; NaO2, 11.5-13.5%; K2O, 1.0-2.0%; Al2O3, ≤0.2%; Fe2O3, ≤0.2%; the remainder is impurities; the diameter of the glass fiber monofilament is 7-10 μm; and the cut length is 3-36 mm.

6. A method for producing alkali-resistant glass fiber water-dispersible chopped yarns, characterized in that: The process steps include: ⑴ Select the following raw materials in weight ratio: quartz sand: 56-65, sodium sulfate: 1-2, limestone: 5-9, zircon sand: 21-28, soda ash: 18-25, fluorite: 0.5-2; (2) After the above raw materials are crushed and mixed, they are added into a stirrer and stirred evenly, and then transported to a melting pool using shrinkage-free zirconium corundum bricks as lining or masonry and melted in natural gas, and then melted at a high temperature of 1600-1700°C and drawn into alkali-resistant glass fiber yarn with a diameter of 7-15μm; ⑶ During the wire drawing process, the surface is coated with a water-dispersible impregnation agent; the water-dispersible impregnation agent is a polymer emulsion composed of an emulsifier, a penetrant, a surfactant, a metal oxide, a dispersant, and water; (4) The drawn alkali-resistant water-dispersible glass fiber raw yarn is naturally conditioned at room temperature to control its surface moisture content at 2-5%; ⑸ Place the conditioned alkali-resistant glass fiber strands neatly on the creel, draw out the strand heads in turn and place them on the chopper to chop them into 3-36mm long water-dispersible chopped fibers; (6) Quickly put the above water-dispersible chopped fibers into a sealed bag to prevent water from evaporating.

7. The method for producing alkali-resistant glass fiber water-dispersed chopped strands according to claim 6, characterized in that: In step (1), the following raw materials are selected in weight ratio: quartz sand: 60-65, sodium sulfate: 1-1.5, limestone: 5-7, zircon sand: 20-25, soda ash: 18-23, fluorite: 0.5-1.

5.

8. A method for producing alkali-resistant glass fiber water-dispersed chopped yarns, characterized in that: The process steps include: ⑴ The selected ingredients are: SiO2, 58-65%; ZrO2, 13.5%-17.5%; CaO, 4.5-7%; NaO2, 11.5-14.5%; K2O, 0.5-2.5%; Al2O3, ≤0.5%; Fe2O3, ≤0.3%; the remainder is impurities, and the diameter is 7-15μm of alkali-resistant glass fiber raw yarn; (2) coating a layer of water-dispersible wetting agent on the surface of the alkali-resistant glass fiber precursor, wherein the water-dispersible wetting agent is a polymer emulsion composed of an emulsifier, a penetrant, a surfactant, a reducing agent, a dispersant, and water; ⑶ The drawn alkali-resistant water-dispersible glass fiber raw yarn is naturally conditioned at room temperature to control its surface moisture content at 2-5%; ⑷ Place the conditioned alkali-resistant glass fiber strands neatly on the creel, draw out the strand heads in turn and place them on the chopper to chop them into 3-36mm long water-dispersible chopped fibers; ⑸ Quickly put the above water-dispersible chopped fibers into a sealed bag to prevent water from evaporating.

9. A water-dispersible sizing agent for alkali-resistant chopped glass fibers, characterized in that: It is composed of emulsifier, penetrant, surfactant, metal oxide, dispersant and water; its component ratio is: Emulsifier: penetrant: surfactant: metal oxide: dispersant: water = 3: 0.8: 4: 2: 0.03: 90; Or: Emulsifier: penetrant: surfactant: metal oxide: dispersant: water = 2.5: 0.6: 5: 1.5: 0.05: 90; Or: Emulsifier: penetrant: surfactant: metal oxide: dispersant: water = 3.5:0.7:3.5:1.0:0.04:

90.

10. Use of the alkali-resistant glass fiber water-dispersible chopped yarn according to any one of claims 1 to 5 in cementing materials.

Citation Information

Patent Citations

  • Method for producing alkali-proof glass fiber

    CN101215079A

  • High-zirconium alkali-resistant glass fiber surface-reinforced short-cut felt and production method thereof

    CN107268180A

  • Carbon fiber sizing agent and preparation process thereof

    CN117684397A

  • Water dispersable glass fiber sizing material

    CN1546408A

  • Glass mat

    JP2003171144A